Lacanian Perspective on Absurdity as an Insoluble Irony in Albert Camus' The Fall - Baskoro, Taufan H (Jurnal Budaya, 2022)
This paper examines the absurdity depicted in Camus' The Fall. Its thesis is that absurdity isjust a discourse without Master Signifier resulting the insoluble irony at its every aspect. Inthis paper I will start by defining the term 'absurdity' and then explain its relation to Lacan'sMaster Signifier. On the next part I will discuss about The Fall and its absurdity which finallyend up with insoluble irony. In the conclusion I argue that absurd condition faced by JeanBaptisteis because he tries to remove Master Signifier which always leads him intocontradictive situation or in other word in insoluble irony.